Literature Review: The Role of Body Flexibility on Heading Ability in Beginner Soccer Players - Hasyim (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study aims to systematically examine the role of body flexibility on heading ability in beginner soccer players. Heading is a fundamental skill in soccer that requires coordination, strength, and body flexibility, particularly in the neck, back, and core muscles. The method used is a systematic literature review with a descriptive qualitative approach based on Cooper's model, and the results are reported using the PRISMA framework. Literature was collected from databases such as Google Scholar, Scopus, and ScienceDirect, with inclusion criteria of articles published between 2013 and 2024, involving players aged 10–17 years, and discussing the variables of flexibility and heading. Of the 94 articles found, 12 were analyzed in depth. The results of the study indicate that body flexibility plays a significant role in improving the effectiveness and safety of heading techniques. Structured flexibility training has been proven to support accuracy, heading power, and reduce the risk of injury. It is concluded that flexibility is an important component in basic soccer training programs and needs to be further investigated empirically.